The Impact of Covid-19 on Tax Compliance Behaviour Among Malaysian Taxpayers - Rani Diana Othman; Zubaidah Ismail; Afidah Sapari; Siti Anis Nadia Abu Bakar (Universitas Negeri Semarang, 2022)
The unexpected Covid-19 crisis presents major challenges to Malaysian’s revenue administrator due to worsening economic conditions as they anticipated growing in tax arrears, loss reporting by business and increasing in tax non-compliance and tax evasion. Therefore the objective of this study is to investigate the impact of the crisis on tax compliance and look at the willingness of the taxpayer to ensure the survival of the country while they themselves are facing financial uncertainty due to the pandemic. Adopting convenient sampling method, a survey was conducted among taxpayers in the south region of Malaysia. The findings show that 28.6% of respondents have deferred their tax e-filing and tax payment during the Covid-19 crisis. Nevertheless, those who have filed, make an early submission with intention to get tax refund in facing potential income reduction. Interestingly, 59.3% of respondents are still willing to pay tax, during and after the Covid-19 period at same marginal tax rate. In conclusion, this study provides important input to the tax administrator on the likelihood of future shortfalls in tax collection and suggests how to minimize the anticipated negative effects of the pandemic.